2016
DOI: 10.2337/dc16-0043
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Serum Prolactin and Prediction of Postpartum β-Cell Function and Risk of Prediabetes/Diabetes

Abstract: OBJECTIVEThe insulin resistance of mid-to late pregnancy poses a physiologic stress test for the pancreatic b-cells, which must respond by markedly increasing their secretion of insulin. This response is achieved through an expansion of b-cell mass induced by the hormones prolactin and human placental lactogen (HPL). Conversely, the furan fatty acid metabolite 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) has recently emerged as a negative regulator of b-cell function in pregnancy. Given their respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 42 publications
6
47
0
1
Order By: Relevance
“…Our findings were consistent with prior prospective data in pregnant and postmenopausal women with short periods of follow-up [19, 20], and were in line with crosssectional observations that higher, but physiologically normal prolactin concentrations were associated with lower type 2 diabetes prevalence [17, 18]. Furthermore, our study demonstrated that the inverse association between prolactin and type 2 diabetes risk in women remained significant after adjustment for a variety of lifestyle and reproductive factors as well as other sex and growth hormones, suggesting that prolactin may be linked to type 2 diabetes through independent pathways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings were consistent with prior prospective data in pregnant and postmenopausal women with short periods of follow-up [19, 20], and were in line with crosssectional observations that higher, but physiologically normal prolactin concentrations were associated with lower type 2 diabetes prevalence [17, 18]. Furthermore, our study demonstrated that the inverse association between prolactin and type 2 diabetes risk in women remained significant after adjustment for a variety of lifestyle and reproductive factors as well as other sex and growth hormones, suggesting that prolactin may be linked to type 2 diabetes through independent pathways.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest a potential role of prolactin in glucose homeostasis. However, long-term prospective data evaluating the relationship between prolactin and future type 2 diabetes risk remain limited, and existing evidence has been inconsistent [1820]. Some studies reported an inverse association between prolactin and type 2 diabetes risk, particularly among women, while a few others reported null or positive associations in men and women combined [1821].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report by Retnakaran et al . 14 suggested that the serum CMPF levels in pregnant women do not predict postpartum insulin sensitivity, insulin resistance, or β cell function three months after delivery. In addition, Lankinen et al .…”
Section: Discussionmentioning
confidence: 99%
“…As such, the histological analysis in our study confirms that SL Dams and MSG Dams present reduced MG development and, probably, milk synthesis. In this regard, studies have demonstrated that the metabolic activity of the MG is a major factor in plasma insulin regulation during the suckling period via a mechanism involving prolactin, the primary hormone in the milk synthesis, and with a known effect on insulin secretion and synthesis [31, 32]. Moreover, the sealing of all teats in dams or litter removal during lactation produces increased plasma insulin levels in lactating dams [33, 34].…”
Section: Discussionmentioning
confidence: 99%